(untitled) (Journal of Atomic and Molecular Sciences, 2016)
Stereodynamics of the title reaction at different reagent vibrational states (v=0-2) are obtained using the quasiclassical trajectory method at collision energy of 0.06 eV on an accurate ^4A" potential energy surface. The vector properties including angular momentum P(θ_r) and P(φ_r) distributions as well as polarization-dependent differential cross sections (PDDCS) of the product CN are presented. Furthermore, the influence of vibrational excitation on the product vector properties has also been studied in present work.